The Effectiveness on job Training Program at the Manpower Department in Reducing Unemployment Rates - Langlang Buana, Prammudya; Purwanti, Dian; Basori, Yana Fajar FY. (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Sukabumi, located in West Java Province, faces serious challenges related to high unemployment rates. This phenomenon is a complex issue that needs to be addressed. One of the solutions that have been proposed and implemented in various regions, including Sukabumi, is the Job Training Program. This research aims to determine the effectiveness of the job training program conducted by the Manpower Office in reducing the unemployment rate in Sukabumi. The research method uses a qualitative approach with a descriptive method. It employs the theory of the